Cell Division Cycle Associated Genes as Diagnostic and Prognostic Biomarkers in Hepatocellular Carcinoma - Jiang, Shan-Shan; Ke, Sheng-Jie; Ke, Zun-Li; Li, Juan; Li, Xiang; Xie, Xing-Wei (Frontiers in Molecular Biosciences, 2021)
With high mortality and poor prognosis, hepatocellular carcinoma (LIHC) has become the fourth leading cause of cancer-related deaths worldwide. Most of the LIHC patients missed the best treatment period because of the untimely diagnosis. For others, even if they are temporarily cured, they have to face a very low prognostic survival rate and a very high risk of recurrence. Based on the characteristics of abnormal proliferation and uncontrolled growth of tumor cells. Cell Division Cycle Associated (CDCA) family genes, which are responsible for regulating the cell cycle and proliferation, were selected as our research object to explore the mechanism of hepatocarcinogenesis. To this end, we investigated the expression profiles of CDCA family genes in LIHC and corresponding normal tissues, and the effect of CDCAs expression on the survival of prognosis and immune cell infiltration through bioinformatics analysis methods and the publicly accessible online databases. In addition, we also analyzed the expression correlation of CDCAs and screened the neighboring genes related to functional CDCAs. The results revealed that the expression levels of CDCA1/3/5/8 were significantly increased in LIHC, regardless of stage, sex, race, drinking behavior, and other clinical factors. CDCAs expression was significantly correlated with poor prognosis and was positively correlated with the infiltration of dendritic cells, B cells, and macrophages. We also found that the most relevant neighboring genes to CDCAs in LIHC were SGO2, NDC80, BIRC5, INCENP, and PLOD1. In general, our work suggests that CDCA1/3/5/8 has the potential to be a diagnostic gene in hepatocarcinogenesis and prognostic biomarkers for LIHC patients.